Addressing salinity intrusion in the polders of coastal Bangladesh: predictive machine-learning modeling for strategic sluice gate operations - Behera, Abhijit; Sena, Dipaka Ranjan; Hasib, Md. R.; Matheswaran, Karthikeyan; Jampani, Mahesh; Mizan, Syed Adil; Islam, Md. J.; Alam, R.; Mondal, M. K.; Sikka, Alok (2024)
The coastal zone of Bangladesh comprises several polders, which are low-lying tracts of land surrounded by embankments to protect against tidal floods and saline water intrusion. They also enhance freshwater availability and aid in improving land productivity. These polders are equipped with sluice gates for water to drain out and intake into the polders. Each sluice has its own catchment area, defined by the elevation and connectivity with canal systems that carry fresh or saline water from surrounding rivers or streams. The sluice gates operation is influenced by in-polder water management for crop cultivation, diurnal tidal dynamics, and the seasonal variations of saline and fresh water in the peripheral river networks. During the dry season, limited flows in the lower Ganges River allow seawater to push inland, causing saltwater intrusion in the peripheral rivers until the rainy season. Community-coordinated sluice gate operations can improve water management, facilitating timely drainage and irrigation, which is essential for high-yielding rice and subsequent dry-season crops. To address these challenges, a multi-variate LSTM (Long Short-Term Memory) model was employed to forecast salinity levels in rivers near 29 sluice gates in a polder near Khulna City in southwest Bangladesh. Utilizing salinity data from July 2011 to December 2022, the models were trained (2011-18) and validated (2018-20) with covariates of discharge, water level, and an upstream reference station. A hierarchical variable additive approach was used to sequentially estimate salinity from upstream to downstream. The NSE was over 0.90 and PBIAS under 5% for all sluice gate locations, confirming accuracy in reconstructing the time series. For forecast testing, the 2020-22 dataset also showed significant confirmation with NSE values over 0.90 and PBIAS under 10%. With readily available input data, the developed salinity forecast model can effectively capture annual and seasonal salinity fluctuations along all sluice gate locations. These forecasting capabilities can potentially identify critical seasonal windows for sluice gate operations, giving the farmers in the polder a 30-day lead time for freshwater intake for irrigation and starting agricultural operations in the aman season.